Electromagnetic wave absorption by metal chalcogenides in modern era - Raja Azadar Hussain (Next Materials)
Electromagnetic wave (EMW) absorbers with very fine matching thickness (d ≤ 1.5 mm), high reflection loss (RL ≤ −50 dB) and wide effective band width (EAB, RL ≤ −10 dB) are needs of the time for radar stealth, electronic components accuracy, medical uses and radiation incidence prevention etc. Carbon based materials have drawbacks of single loss mechanism and impedance mismatch due to high conductivity whereas metallic absorbers have very narrow absorption bandwidth. Metal chalcogenides have been aimed for EMW absorption in the last decade due to their unique properties such as tunable band gap, high absorption coefficient, easy manufacturing, thermal and electrical properties. This article reviews the EMW absorption of metal chalcogenides and their composites with carbon (nanotubes, graphenes, hollow microspheres, sheets, polymers etc.), and non-carbon materials (metals, oxides, sulfides, selenides and tellurides). Our aim is to compare EMW absorption performances of materials with their composition and structures.